Impact of early SGLT2 inhibitors prescription on acute decompensated heart failure outcomes: insights from a real-world setting - Echeverría, Luis Eduardo; Rojas, Lyda Z.; Serrano-García, Angie Yarlady; Botero, Daniel R.; Cantillo-Reines, María; Jurado, Adriana M.; García-Rueda, Karen Andrea; Torres-Bustamante, Ángela; Cañón-Gómez, Diana Ivonne; Idrovo-Turbay, Carolina; Sánchez-García, Robinson; Alberto Rodríguez, Jaime; et al. (Revista española de cardiología. English version, 2025)
Introduction and objectives - Although sodium-glucose cotransporter 2 inhibitors (SGLT2i) have shown benefits in acute decompensated heart failure (ADHF), the extrapolability of clinical trial results to general populations remains limited. This study evaluated the impact of early in-hospital SGLT2i prescription on ADHF outcomes in a real-world setting. - Methods - Prospective cohort study. Adults with ADHF from a third-level cardiovascular center were included. The primary analysis compared early SGLT2i (prescribed within 48hours of admission) versus late SGLT2i (prescribed after 48hours). A secondary analysis included patients not receiving in-hospital SGLT2i. The primary outcome was in-hospital mortality. Secondary outcomes included the length of hospital stay, 30-day improvement in the Minnesota Living with Heart Failure Questionnaire score, 30-day rehospitalization due to heart failure, and 30-day all-cause mortality. - Results - Of 2016 patients, early SGLT2i (≤ 48h) was initiated in 1275 (63.2%) patients, late SGLT2i in 346 (17.2%), and 395 (19.6%) did not receive in-hospital SGLT2i. After multivariate adjustment, early versus late SGLT2i use was associated with decreased in-hospital mortality (RR, 0.37; 95%CI, 0.17-0.77) and reduced hospital stay (mean difference −5.70 days; 95%CI, −7.05 to −4.34). Similarly, early versus late or no in-hospital SGLT2i use was associated with decreased in-hospital mortality (RR, 0.25; 95%CI, 0.14-0.44), reduced hospital stay (mean difference −2.99 days; 95%CI, −4.05 to −1.92), and lower 30-day combined mortality/heart failure rehospitalization (RR, 0.72; 95%CI, 0.53-0.98). - Conclusions - Early in-hospital SGLT2i prescription was associated with improved cardiovascular outcomes in ADHF in a real-world setting. - Resumen - Introducción y objetivos - Aunque los inhibidores del cotransportador de sodio-glucosa tipo 2 (iSGLT2) han mostrado beneficios en la insuficiencia cardiaca aguda descompensada (ICAD), la extrapolabilidad de los beneficios observados en los ensayos clínicos a la población general sigue siendo limitada. Este estudio evaluó el impacto de la prescripción temprana de iSGLT2 durante la estancia hospitalaria sobre los desenlaces de la ICAD en un contexto del mundo real. - Métodos - Estudio de cohorte prospectiva. Se incluyeron adultos con ICAD de un centro cardiovascular de tercer nivel. El análisis primario comparó iSGLT2 temprano (prescrito en las 48 horas siguientes al ingreso) frente a iSGLT2 tardío (prescrito después de 48 horas). Un análisis secundario incluyó a los pacientes que no recibieron iSGLT2 durante su estancia. El desenlace primario fue la mortalidad intrahospitalaria. Los desenlaces secundarios incluyeron la duración de la estancia hospitalaria, la mejoría a los 30 días en la puntuación del Minnesota Living with Heart Failure Questionnaire, la rehospitalización a los 30 días por IC y la mortalidad por todas las causas a los 30 días. - Resultados - De 2.016 pacientes, se inició iSGLT2 temprano (≤ 48h) en 1.275 (63,2%) pacientes, iSGLT2 tardío en 346 (17,2%), y 395 (19,6%) no recibieron iSGLT2 intrahospitalario. Tras el ajuste multivariante, el uso temprano frente al tardío de iSGLT2 se asoció con una disminución de la mortalidad intrahospitalaria (RR=0,37; IC95%, 0,17-0,77) y una reducción de la estancia hospitalaria (diferencia media −5,70 días; IC95%, −7,05 a −4,34). Del mismo modo, el uso temprano de iSGLT2 en comparación con el uso tardío o la ausencia de uso se asoció con una disminución de la mortalidad hospitalaria (RR=0,25; IC95%, 0,14-0,44), una reducción de la estancia hospitalaria (diferencia media −2,99 días; IC95%, −4,05 a −1,92) y una reducción de la combinación de mortalidad y rehospitalización por IC a los 30 días (RR=0,72; IC95%, 0,53-0,98). - Conclusiones - La prescripción temprana intrahospitalaria de iSGLT2 se asoció con mejores desenlaces cardiovasculares en la ICAD en un contexto del mundo real.
Gesehen am 21.01.2026